Choosing your companion: how locus of control shapes responses to AI vs. real pets - Gong, Shuhui (Elsevier, 2026)
AI pets hold considerable market potential as companions, yet research on them remains limited. Individual personality traits are known to shape preferences for biological pets, such as the extroversion of dog owners and the openness and neuroticism of cat owners. However, whether this influence extends to AI pets remains unclear. This study addresses this gap by examining how the locus of control shapes individuals' responses to AI versus real pets through the lens of attribution theory. The findings demonstrate that individuals with an internal locus of control showed no significant preference between pet types, whereas those with an external locus of control were more inclined toward AI pets in terms of both attitudes and purchase intentions. Desire for control emerged as a key mediator: its mediating effect on consumption was more pronounced among individuals with an external locus of control, even though individuals with an internal locus of control generally reported a stronger overall desire for control. These results enrich the literature on individual differences, extend the application of the concept of the locus of control and attribution theory to the context of AI pets, and offer practical insights for AI pet marketing and product design.